3D effects on transport and plasma control in the TJ-II stellarator. (9th August 2017) - Castejón, F.; Alegre, D.; Alonso, A.; Alonso, J.; Ascasíbar, E.; Baciero, A.; de Bustos, A.; Baiao, D.; Barcala, J.M.; Blanco, E.; Borchardt, M.; Botija, J.; et al.
Abstract: The effects of 3D geometry are explored in TJ-II from two relevant points of view: neoclassical transport and modification of stability and dispersion relation of waves. Particle fuelling and impurity transport are studied considering the 3D transport properties, paying attention to both neoclassical transport and other possible mechanisms. The effects of the 3D magnetic topology on stability, confinement and Alfvén Eigenmodes properties are also explored, showing the possibility of controlling Alfvén modes by modifying the configuration; the onset of modes similar to geodesic acoustic modes are driven by fast electrons or fast ions; and the weak effect of magnetic well on confinement. Finally, we show innovative power exhaust scenarios using liquid metals.